Prevalence of Escherichia coli O157:H7 and Enterobacteriaceae on hands of workers in Halal cattle Abattoirs in Peninsular Malaysia - Mohd Tamrin, Shamsul Bahri; Tukur, Muhammad Adamu; Mohd Desa, Mohd Nasir; Bejo, Siti Khairani (Penerbit Universiti Sains Malaysia, 2016)
Background: Several occupational diseases of multiple origins are encountered among abattoir workers. Presence of indicator microorganisms (coliforms) on hands of workers can be used a gauge for hygienic practices. Methods: A cross-sectional study was performed to assess the prevalence of E.coli and enterobacteriaceae among Halal abattoir workers in some government halal abattoirs of Malaysia. A total of one hundred and sixty-five hand swab samples were collected from workers of Halal abattoirs in Malaysia. The samples were subjected to microbiological analysis for characterisation and serotyping. Results: The results have shown that no Escherichia coli O157:H7 was isolated on the hands of abattoir workers before and after work. However, a total prevalence of 9.7% was recorded for all samples during work. For non-O157:H7, total prevalence of 33.3% during work and 13% after work were obtained. High prevalence was recorded in sample taken during work from Tampin, Jasin and Kemaman (100% each) while low prevalence where observed in Shah Alam, Banting and Ipoh (20% each). Conclusions: Based on the findings the hygienic practices of hand washing among the workers in few locations was found to be low especially after work.